A Statement by President Clark - Clark, Robert D.:::Creator::::::::::::; Larry Jamison, Jim Kioski, Dave Manard, Al Dubiel:::Contributor:::::::::::: (San Jose State College)
In this publication "A Statement by Dr. Robert D. Clark, President, San Jose State College," President Clark examines the college climate at SJSC and explains his understanding of the current protest and the need to maintain law and order while permitting expression of free speech. The issues confronting SJSC and other college campuses across the nation included the Vietnam War, anti-war protests against the draft, the war, Capitalism, the presence of DOW Chemical on campus and the ROTC, and free speech.